Enabling smallholder farmers' competitiveness in the market: Productivity and agroenterprise development innovations in Tanzania - Pan-Africa Bean Research Alliance (International Center for Tropical Agriculture, 2001)
Background: The Traditional Irrigation and Environment Development Organisation (TIP) is a non profit making non governmental organisation registered in Tanzania since August 1999. The objective is to improve income and livelihoods of smallholder farmers through traditional irrigation project work in Northern Tanzania. Despite notable increases in agricultural production and improved productivity as a result of improved irrigation of crops; poverty and poor living conditions have persisted in those areas, partly because smallholder farmers have not had access to reliable domestic and export markets. Recognising their respective strengths in the area of rural innovation, CIAT - Africa and TIP entered into a collaborative arrangement in 2001 with a view to addressing the market challenges facing smallholder farmers. In this arrangement, CIAT introduced an institutional innovation titled “Market Access and Agroenterprise Development (MAAD)” approach